Level of knowledge, attitude and practice of family planning among public secondary school teachers in Enugu east senatorial districts, Nigeria - Onyinye, Okafor Charles (2021)
In developing nations, family planning inadequacies are the major cause of poverty, ill health, poor economic development, and political instability. Adequate family planning utilization could save about $5.7 billion by preventing unintended pregnancies and unsafe abortions. However, adoption of any family planning method requires prior knowledge. A good knowledge of the use of family planning methods and their benefits/side effects depends on the effectiveness of the counselling and sensitization of the risk population. The objectives of this study are to determine the level of knowledge, attitude, and ever practice family planning and its associated factors among public secondary school teachers in Enugu east senatorial districts Nigeria. A crosssectional study conducted among public secondary school teachers in Enugu east senatorial districts, Nigeria. All eligible teachers aged 18-60 years old were included in this study. A total of 1000 self- administered questionnaires were distributed. Chi-square test and simple logistic regression were used to identify the factors associated with levels of knowledge, attitudes, and ever practice family planning among the respondents. Binary Logistic Regression was used to determine the predictors of good knowledge, positive attitudes, and ever practices family planning. All hypothesis tests were two-sided, and the level of significance was set at 0.05. The total number of respondents included was 1000 and the response rate was 100%. The majority (61.3%) of the respondent had good knowledge of family planning while more than half of the respondents (52.7%) had positive attitudes towards family planning, and about 55.0% of them had ever practice family planning. Furthermore, factors which were significantly associated with levels of knowledge, attitudes, and ever practice family planning includes some variables from socio-demographic characteristic, sources of information, partner involvement, history of family planning and healthcare facilities. Binary logistic regression analysis showed the significant predictor of good knowledge; being a female (AOR=0.48 95%CI 0.34-0.67), other ethnic groups (Hausa and Yoruba) (AOR= 5.33: 95%CI: 2.77–10.25). A significant predictor of positive attitude was the age group 38 years and above (AOR=2.40: 95%CI: 1.78–3.24), having a bachelor's degree in education (AOR=6.74: 95%CI: 2.82-16.08). For, ever practiced family planning includes those with 3 children and above (AOR=3.46: 95%CI: 2.09– 5.71), and getting health information from the radio (AOR=2.56: 95%CI: 1.56– 4.19). Conclusively, the respondent’s levels of knowledge, attitude and ever practice of family planning are moderate. However, family planning educational workshop is recommended to improve the teacher knowledge on family planning, also to increase awareness on the important family planning using social media as a channel.